(untitled) (Vietnam Journal of Community Medicine, 2024)
To effectively implement a management method like 5S and improve quality, an important condition is to improve employees’ knowledge about quality. Currently, there are very few studies evaluating knowledge of 5S application in hospitals, from which to serve as a basis for improvement activities. Objective: Compare the change in knowledge about 5S of medical staff at Can Tho University of Medicine and Pharmacy Hospital after one year of intervention. Research method: Intervention study, pre- and post-intervention assessment, sampling of all medical staff at Can Tho University of Medicine and Pharmacy Hospital. Use JICA’s 5S checklist. Results: After one year of intervention, the proportion of health workers with good knowledge of 5S in 5 areas increased compared to the initial survey. In particular, the study found a statistically significant change in the field of “Screening”, increasing from 49.8% to 56.08% with p = 0.038; The field “Care” increased from 64.3% to 67.84% with p=0.042; and the “Readiness” domain increased from 66.3% to 69.41% with p=0.036. Conclusion: The study shows that the intervention effectiveness of improving knowledge about 5S has practical significance, contributing to the hospital’s quality improvement activities.